Cosmological Parameters from Planck Data in SU(2)CMB, Their Local ΛCDM Values, and the Modified Photon Boltzmann Equation - Hofmann, Ralf; Meinert, Janning; Balaji, Shyam Sunder (Annalen der Physik, 2023)
A review of the spatially flat cosmological model SU(2)CMB, minimally induced by the postulate that the cosmic microwave background (CMB) is subject to an SU(2) rather than a U(1) gauge principle, is given. Cosmological parameter values, which are determined from the Planck CMB power spectra at small angular scales, are compared to their values in spatially flat ΛCDM from both local and global extractions. As a global model SU(2)CMB leans toward local ΛCDM cosmology and is in tension with some global ΛCDM parameter values. Spectral antiscreening / screening effects in SU(2)CMB radiance are presented within the Rayleigh– Jeans regime in dependence on temperature and frequency. Such radiance anomalies can cause CMB large‐angle anomalies. Therefore, it is pointed out how SU(2)CMB modifies the Boltzmann equation  for the perturbations of the photon phase space distribution at low redshift and why this requires to the solve the ℓ‐hierarchy on a comoving momentum grid (q‐grid) for all z. Implications for the cosmological model are explored of the assumption that the cosmic microwave background is subject to an SU(2) Yang– Mills theory of scale 10−4 eV rather than U(1) quantum thermodynamics. This concerns zeroth‐order (changes at high redshifts) and first‐order cosmological perturbations (changes at high and low redshifts). Technical obstacles (q‐grid) are pointed out in treating the latter by Boltzmann codes.